Indonesian Interferences Toward English Status on Facebook - Sihindun Arumi; Giyatmi Giyatmi; Ratih Wijaya; Purwani Indri Astuti (Universitas Cokroaminoto Palopo, 2021)
It was such a descriptive qualitative research that aims at describing the occurrence of the interference of Indonesian language toward facebook status in English language. The data were the words, phrases or sentences containing Indonesian interference toward English status on facebook. The source of the data was the statuses on the researchers’ facebook home. The data were collected through observation and documentation. Observation was carried out by observing the words on the facebook statuses using English language. They then were documented by applying print screen (capturing the picture using computer) or screen shoot (capturing the picture using cellphone). The result of the research showed the occurrence of 3 types of Indonesian interference on English status on facebook, namely lexical, morphological, and syntactical interference. However, syntactical interference mostly occurred on English status on facebook that appeared in the forms of subject-verb agreement (ellipsis be, negative forms), parallelism (verb and adjective), and verb use (verb as complement, construction of preposition and verb, construction of modal and verb, construction of verb and adverb, and tenses).